2015
DOI: 10.1111/acem.12616
|View full text |Cite
|
Sign up to set email alerts
|

Process Quality Indicators Targeting Cognitive Impairment to Support Quality of Care for Older People with Cognitive Impairment in Emergency Departments

Abstract: Objectives: The objective of this study was to develop process quality indicators (PQIs) to support the improvement of care services for older people with cognitive impairment in emergency departments (ED).Methods: A structured research approach was taken for the development of PQIs for the care of older people with cognitive impairment in EDs, including combining available evidence with expert opinion (phase 1), a field study (phase 2), and formal voting (phase 3). A systematic review of the literature identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
(63 reference statements)
0
34
0
1
Order By: Relevance
“…Because numerous studies have demonstrated deficiencies in ED care for older adults 36,37 with falls, 38 dementia, 39,40 or delirium, 40 a concern exists that …”
Section: Discussionmentioning
confidence: 99%
“…Because numerous studies have demonstrated deficiencies in ED care for older adults 36,37 with falls, 38 dementia, 39,40 or delirium, 40 a concern exists that …”
Section: Discussionmentioning
confidence: 99%
“…This care concept as a SQI triggered in none of the participating EDs and, yet, some EDs did use a screening tool (though minimal). Therefore, in recognition of the importance of screening, the companion process quality indicator set 31 includes screening as a measure of care. SQI = structural quality indicator.…”
Section: Discussionmentioning
confidence: 99%
“…If quality indicators are effective in stimulating change in practice, then they have a limited life span; after a period of implementation, existing indicators should be reevaluated to ensure that the point of difference in quality across hospitals is still being targeted. Figure 1 gives an overview of process 28,31,32 and outcome quality indicators for the care of older ED patients with cognitive impairment. This study (a subset of the primary study) focused on the development of SQIs targeting the special needs of the older ED population with cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Academic Emergency Medicine, Schnitker et al 10,11 succeed in pushing the evidence base further and addressing our understanding of older people's issues. Their two articles empirically and quantitatively evaluate quality care for older patients who present to the ED with cognitive impairment.…”
mentioning
confidence: 99%